Antifungal constituents from the stems of Dracaena cambodiana - Kiem et al, Phan Van (Vietnam Journal of Chemistry, 2014)
The stems of Dracaena cambodiana have been investigated for antifungal constituents, resulting in the isolation of a new steroidal saponin dracagenin A (1) together with two known components 25S-namogenin B (2) and spriroconazole A (3). Their structures were elucidated on the basis of extensive spectroscopic analysis including 1D, 2D NMR and ESI MS. The isolated compounds were evaluated for their antifungal activities. 1 and 3 exhibited inhibitory activity against Aspergilus niger at the MICs of 50 mg/ml. No inhibition effects on F. oxysporum, S. cerevisiae and C. albicans have been found for the tested compounds. Interestingly, toxicity of 3 towards several cancer cell lines has been demonstrated. The IC50 of 3 against Hep-2, Lu, and RD are 2.002, 4.727, and 4.029 mg/ml, respectively.